Black Lives Matter, a Princess from Zanzibar, Bismarck, and German Memorial Hygiene - Neumann, K. (German Politics and Society, 2022)
Following the surge of the Black Lives Matter movement in the wake of George Floyd’s murder on 25 May 2020, memorials in remembrance of individuals implicated in colonialism or slavery have come under increasing attack. This article discusses and contextualizes challenges in 2020 to the memorialization of Otto von Bismarck (1815–1898) and Emily Ruete née Salama bint Said (1844–1924) in Hamburg, where the legacy of the German colonial past is particularly palpable. The article argues that proposed solutions—be it the demolition of the city’s main Bismarck monument, its restoration and the erection of a counter-memorial adjacent to it, or the un-naming of a street named after Ruete—potentially erase the complexities and contradictions of the lives of historical actors, are often informed by a desire to quarantine the past, and, just as often, fail to engage with its continuation in the present.
Keywords: Bint Said, Salama (1844-1924)